'Age is just a number': Articulating the cultural dimension of child labour in Africa's small-scale mining sector. (September 2022) - Gatsinzi, Angelique; Hilson, Gavin
Abstract: This paper engages critically with socio-cultural debates on child labour in sub-Saharan Africa, with a view toward articulating more comprehensively why young boys and girls pursue so-called 'hazardous' work in the region's artisanal and small-scale mining (ASM) sector. Today, a discourse of 'forced (child) labour' propelled by images of, and anecdotal claims made about, the ASM sector is being widely promoted across sub-Saharan Africa, despite little being known about the social context within which the region's children live. Drawing on a qualitative case study of child labour in Ghana's ASM sector, it is argued that, at the community level, views on maturity and readiness to enter the labour market contrast sharply with the ideas underpinning the concept of 'childhood' at the heart of legal and policy frameworks for child protection and child labour eradication. Both have historical roots in Western elite and middle-class milieus. Highlights: The paper engages critically with socio-cultural debates on child labour in sub-Saharan Africa. Critically examines the discourse propagated by donors on the Worst Forms of Child Labour (WFCL). Argues that Western perceptions and African perceptions of the WFCL differ markedly. Examines the cultural dimension of child labour in the context of artisanal and small-scale mining (ASM) in Africa. Draws on research carried out on child labour in ASM in Ghana.